Unleashing the Synergy between Human Values and Digital Innovation: A Holistic Framework for Sustainable Future Management Education - Kanimozhi Ganesan (Cadmus)
In an age marked by digital transformation and global uncertainty, traditional management education remains helpful but no longer sufficient to prepare leaders for the challenges ahead. This paper proposes a holistic framework that integrates human values with digital innovation to create a future-ready paradigm for business education. Built on a strong foundation of ethics, compassion, environmental care, and technological proficiency, our framework introduces Seven Transformative Educational Pillars and Five Engines of Sustainable Business Development. These elements serve as a blueprint for cultivating conscious, adaptive, and impact-driven leaders. By drawing on ideas from systems thinking, emotional intelligence, and stakeholder theory, as well as lessons learned from hands-on, real-world experiences, the paper highlights real-world applications through global case studies from organizations like Google, Unilever, Patagonia, Amazon, and Zappos. It not only presents these cases as sources of knowledge but also reveals the hidden values these companies uphold during pivotal decision-making moments. By uniting humanistic principles with emerging innovations, the paper offers a visionary yet actionable roadmap for reimagining management education in a rapidly changing world.